Evidence of a Demethylase-Independent Role for the H3K4-Specific Histone Demethylases in Aspergillus nidulans and Fusarium graminearum Secondary Metabolism - Bachleitner, Simone; Sørensen, Jens Laurids; Gacek-Matthews, Agnieszka; Sulyok, Michael; Studt, Lena; Strauss, Joseph (Frontiers in Microbiology, 2019)
Fungi produce a plethora of secondary metabolites (SMs) involved in cellular protection, defense and signaling. Like other metabolic processes, transcription of SM biosynthesis genes is tightly regulated to prevent an unnecessary use of resources. Genes involved in SM biosynthesis are usually physically linked, arranged in secondary metabolite gene clusters (SMGCs). Research over the last decades has shown that chromatin structure and posttranslational modifications (PTMs) of histones represent important layers of SMGC regulation. For instance, trimethylation of histone H3 lysine 4 (H3K4me3) is a PTM typically associated with promoter regions of actively transcribed genes. Previously, we have shown that the H3K4me3-specific, JmjC domain-containing histone demethylase KdmB functions in repression but also in activation of secondary metabolism in Aspergillus nidulans, suggesting that KdmB has additional functions apart from histone demethylation. In this study, we identified demethylase-independent functions of KdmB in transcriptional regulation of SM gene clusters. Furthermore, we show that this activating and demethylase-independent role of the H3K4 demethylase is also conserved in the phytopathogenic fungus Fusarium graminearum. Lack of FgKdm5 resulted in significant downregulation of 5 out of 7 analyzed SMs, whereby only one SMGC depends on a functional JmjC-domain. In A. nidulans strains deficient in H3K4 methylation, i.e cclA∆, largely phenocopied kdmB∆ in A. nidulans, while this is not the case for most of the SMs analyzed in Fusarium spp. Notably, KdmB could not rescue the demethylase function in ∆fgkdm5, but restored all demethylase-independent phenotypes.